Medicaid expansion and inpatient hospital charges among women with major depressive disorders - Oluwasegun Akinyemi; Mojisola Fasokun; Fadeke Ogunyankin; Gabriella Kuffour; Samar K. Khalil; Ofure Omokhodion; Rachael Oyebade; Chioma Ekwunazu; Ayomide Ogunsakin; Miriam Michael; Guoyang Luo (PLoS ONE, 2026)
Objective To examine the association between Medicaid expansion under the Affordable Care Act (ACA) and total inpatient hospital charges among women hospitalized with major depressive disorder (MDD), comparing Maryland and New Jersey, two Medicaid expansion states with distinct payment systems, to Florida, a non-expansion state. Methods We conducted a retrospective cohort study using data from the State Inpatient Databases for Maryland, New Jersey, and Florida from 2007 to 2020. The study population included women aged 18–64 years admitted with a primary diagnosis of MDD. The pre-ACA period was defined as 2007–2013, and the post-ACA period as 2014–2020. Difference-in-differences (DID) models with robust standard errors were used to estimate changes in total inpatient hospital charges, adjusting for demographic, socioeconomic, and clinical characteristics. Stratified analyses by race/ethnicity and insurance type were conducted to assess heterogeneity in policy effects. Results In adjusted analyses, Medicaid expansion was associated with divergent changes in hospital charges across expansion states. Compared with Florida, Maryland experienced a relative post-ACA reduction (DID estimate − $2,313; 95% CI: − $2,549 to −$2,078). In contrast, New Jersey had a post-ACA increase (+$3,366; 95% CI: $2,746 to $3,987). In Maryland, post-ACA reductions were observed across all racial and ethnic groups and insurance categories, with the largest decreases among uninsured and Medicaid-covered patients. New Jersey demonstrated heterogeneous patterns, including charge increases across most payer groups. Conclusion The effects of Medicaid expansion on inpatient charges among women with MDD differed across states, reflecting variations in payment regulation and hospital pricing. Maryland’s reductions suggest that coupling coverage expansion with cost‑containment mechanisms may help constrain hospital charge growth, with potential implications for the financial burden of mental health care.